(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The delay in the beginning of the university academic year for first-year students caused by the COVID-19 pandemic in Cuba, causes an increase in the loss of learning by the student. For this reason, it was decided to provide a course that delves into the contents and mathematical skills of the previous teaching, in the non-face-to-face course modality -in virtual space- for the students of the Faculty of Economics of the University of Havana. This work outlined the objective of assessing the actions carried out, the experiences and impacts of the Mathematics Propedeutic Course, as well as the recommendations for future courses. For this, the actions to be carried out to achieve the course were explained; Subsequently, the experiences when teaching the course were exposed, pointing out the impacts that teachers and students faced. Finally, some measures are recommended for the improvement of the course which leads to reduce learning losses.